Relationship between pedal force asymmetry and performance in cycling time trial - Bini, R. R.; Hume, P. A. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: It remains unclear if cyclists with better performance have less asymmetry. Therefore, this study aimed at assessing the relationship between cycling time trial performance and bilateral asymmetries in pedal forces.